Supporting designers: moving from method menagerie to method ecosystem. (2020) - Gericke, Kilian; Eckert, Claudia; Campean, Felician; Clarkson, P. John; Flening, Elias; Isaksson, Ola; Kipouros, Timos; Kokkolaras, Michael; Köhler, Christian; Panarotto, Massimo; Wilmsen, Miriam
Abstract: Supporting designers is one of the main motivations for design research. However, there is an ongoing debate about the ability of design research to transfer its results, which are often provided in form of design methods, into practice. This article takes the position that the transfer of design methods alone is not an appropriate indicator for assessing the impact of design research by discussing alternative pathways for impacting design practice. Impact is created by different means – first of all through the students that are trained based on the research results including design methods and tools and by the systematic way of thinking they acquired that comes along with being involved with research in this area. Despite having a considerable impact on practice, this article takes the position that the transfer of methods can be improved by moving from cultivating method menageries to facilitating the evolution of method ecosystems. It explains what is understood by a method ecosystem and discusses implications for developing future design methods and for improving existing methods. This paper takes the position that efforts on improving and maturing existing design methods should be raised to satisfy the needs of designers and to truly support them.